Vulnerability characteristics and adaptation strategies of public health systems in different regions of China - Teng, Yajun; Cao, Yue; Feng, Shuai; Han, Bin; Gao, Qinfen; Li, Zengzheng (Frontiers in Public Health, 2025)
Global climate change, urbanization, and environmental pollution have significantly altered the ecosystem and socio-economic structure, while also promoting a new disease risk pattern that has markedly affected human physical and mental health, increasing the complexity and uncertainty of disease control and prevention. This review aims to summarize the correlation between unique public health vulnerabilities and disease distribution in different regions of China by investigating the national and regional personalized response strategies and research progress.